The Age Aspect of Etiopathogenetic and Clinico-morphological Features of Chronic Gastritis - Anna Berestova (Journal of Global Pharma Technology, 2019)
Chronic gastritis (CG) is a histopathologic entity characterized by chronic inflammation of the gastric mucosa with loss of gastric glandular cells. CG, pathological regeneration of the gastric mucosa, intestinal metaplasia (IM), and intraepithelial neoplasia or epithelial dysplasia (ED) of the stomach are common and are associated with an increased risk of gastric cancer. 800 patients (aged 8 to 80) were examined during the period of 2012-2017. Patients with CAG were diagnosed by endoscopy then underwent histological, bacteriological and cytological examinations. The Enzyme-Linked Immunosorbent Assay (ELISA) was used to detect antibodies to H+/K+ -ATPase and to Castle factors of parietal cells of the gastric mucosa in serum.Keywords: Helicobacter pylori (H. pylori) infection; Enzyme-Linked Immunosorbent Assay; gastric glandular cells.